Implementation of LMS Viska Learning on Motivation and Learning Achievement of Class XI OTKP Students of Vocational High School - Yuhana, Nurul (Universitas Muhammadiyah Mataram, 2023)
Abstract : The changes that occur in the education aspect, namely learning models and learning media, encourage SMK Negeri 6 Surakarta to use the Viska Learning Learning Management System (LMS) product as a medium for the learning process between teachers and students. The purpose of the study was to determine the effect of LMS Viska Learning on the motivation and learning achievement of students in the Financial OTK subjects of class XI OTKP Vocational High School 6 Surakarta. The research method used is descriptive quantitative research with research instruments using questionnaires and questions midterm and final exam. The results showed that there were 74.76% HM, 15.88% MM, and 9.34% LM. Student achievement in use of LMS Viska Learning shows the range of values for one semester. Based on the distribution of scores in each range, it shows that LMS Viska Learning has had a positive impact on students in class XI OTKP 1, 2, and 3. From a total of 107 students, scores in the range II – IV have decreased. While in the range of values of V, there was a significant increase. Utilization of Viska Learning LMS in the learning process can increase high learning motivation to achieve good achievements effectively.